Differential Expression Profiles and Functional Prediction of Circular RNAs and Long Non-coding RNAs in the Hippocampus of Nrf2-Knockout Mice - Zhang, Run-Jiao; Li, Yan; Liu, Qing; Gao, Yan-Jing; Du, Juan; Ma, Jun; Sun, Shao-Guang; Wang, Lei (Frontiers in Molecular Neuroscience, 2019)
Background: Nrf2 (nuclear factor, erythroid 2 like 2) is believed to play a major role in neurodegenerative diseases. The present study attempted to investigate the hippocampal circRNA and lncRNA expression profiles associated with Nrf2-mediated neuroprotection. Methods: The hippocampal mRNA, circRNA and lncRNA expression profiles of Nrf2 (-/-) mice were determined by microarray analysis. Bioinformatics analyses, including identification of differentially expressed mRNAs (DEmRNAs), circRNAs (DEcircRNAs) and lncRNAs (DElncRNAs), DEcircRNA-miRNA-DEmRNA interaction network construction, DElncRNA-DEmRNA co-expression network construction, and biological function annotation, were conducted. Quantitative real-time polymerase chain reaction (qRT-PCR) was performed to validate the dysregulated expression of circRNAs and lncRNAs derived from the microarray data of the hippocampus of Nrf2 (-/-) mice. Results: Compared to wild-type Nrf2 (+/+) mice, 412 DEmRNAs (109 up- and 303 down-regulated mRNAs), 1279 DEcircRNAs (632 up- and 647 down-regulated circRNAs), and 303 DElncRNAs (50 up- and 253 down-regulated lncRNAs) were identified in the hippocampus of Nrf2 (-/-) mice. Additionally, in qRT-PCR validation results, the expression patterns of selected DEcircRNAs and DElncRNAs were generally consistent with results in the microarray data. The DEcircRNA-miRNA-DEmRNA interaction networks revealed that mmu_circRNA_44531, mmu_circRNA_34132, mmu_circRNA_000903, mmu_circRNA_018676, mmu_circRNA_45901, mmu_circRNA_33836, mmu_circRNA_34137, mmu_circRNA_34106, mmu_circRNA_008691, and mmu_circRNA_003237 were predicted to compete with 47, 54, 45, 57, 63, 81, 121, 85, 181, and 43 DEmRNAs, respectively. ENSMUST00000125413, NR_028123, uc008nfy.1, AK076764, AK142725, AK080547 and AK035903 were co-expressed with 178, 89, 149, 179, 142, 55 and 112 DEmRNAs in the Nrf2 (-/-) hippocampus, respectively. Conclusions: In conclusion, our study might contribute to exploring the key circRNAs and lncRNAs associated with Nrf2-mediated neuroprotection.